2015
DOI: 10.1186/s12903-015-0018-6
|View full text |Cite
|
Sign up to set email alerts
|

Different contribution of BRINP3 gene in chronic periodontitis and peri-implantitis: a cross-sectional study

Abstract: BackgroundPeri-implantitis is a chronic inflammation, resulting in loss of supporting bone around implants. Chronic periodontitis is a risk indicator for implant failure. Both diseases have a common etiology regarding inflammatory destructive response. BRINP3 gene is associated with aggressive periodontitis. However, is still unclear if chronic periodontitis and peri-implantitis have the same genetic background.The aim of this work was to investigate the association between BRINP3 genetic variation (rs1342913 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…The literature supports the evidence that SNPs play an important role in the transcription of these inflammatory mediators and may influence the osseointegration success, including single‐nucleotide polymorphism (SNPs) in MMPs …”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The literature supports the evidence that SNPs play an important role in the transcription of these inflammatory mediators and may influence the osseointegration success, including single‐nucleotide polymorphism (SNPs) in MMPs …”
Section: Discussionmentioning
confidence: 57%
“…20 Moreover, an intense inflammatory process is mediated by cytokines that point to different cell types and stimulating the production of prostaglandins and MMPs, which are associated with bone and connective tissue breakdown. 21 The literature supports the evidence that SNPs play an important role in the transcription of these inflammatory mediators and may influence the osseointegration success, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] including singlenucleotide polymorphism (SNPs) in MMPs. [8][9][10] An important point to validate the association between polymorphism and pathological processes is a methodological and study design restricted.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“… There is high level of RANKL/OPG in peri‐implant mucosae of patients with history of chronic periodontitis (Costa et al., ). Haplotypes in BMP4 and FGF genes increase the risk of peri‐implantitis (Coelho et al., ) MMP13 , TIMP2, and TGFB3 gene polymorphisms are associated with Brazilian chronic periodontitis and peri‐implantitis (Junior et al., ). BRINP3 gene has different contribution in chronic periodontitis and peri‐implantitis (Casado et al., ). IL6 gene polymorphism is associated with periodontitis and peri‐implantitis in a Brazilian population (Casado et al., ,b). …”
Section: Periodontitis and Peri‐implant Diseasesmentioning
confidence: 99%
“…11 Targeted fine-mapping work identified BRINP3, in 1q31.3, as associated with aggressive periodontitis, 12 and later, this result was replicated in cohorts with chronic periodontitis and peri-implantitis. 13,14 Interestingly, the GWAS study that identified GLT6D1 as associated with aggressive periodontitis 2 showed P-values ranging from 0.0001 to 0.0003 for markers close to BRINP3 (Table 1). This scenario is likely an example that suggests that it may be an oversimplification to just consider GWAS as the main source of believable genetic signals for periodontitis.…”
mentioning
confidence: 99%